Zalafeed: High Fiber and Protein Husbandry Ingredient from Salak Waste Industries - Khairul Farihan, Kasim (Malaysian Invention and Design Society (MINDS), 2010)
Khairul Farihan Kasim and his team won bronze at ITEX 2007, 18th - 20th May 2007 was held at Kuala Lumpur Convention Centre (KLCC), Kuala Lumpur.